HISTORY OF URANIUM DEALS - IN THE EXAMPLE OF UCHKUDUQ - Ilyos Abdikomilovich (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Since the beginning of the 20th century, geologists have carried out large-scale geological exploration work to discover uranium deposits in Central Asia. In the 20-60s of the last century, as a result of scientific research conducted by Soviet geologists in this area, large uranium deposits were discovered and enterprises for their processing were launched. The article analyzes the work carried out by foreign and local researchers to shed light on the history of uranium deposits in the region following the discovery of the Uchkuduk uranium deposit.